2021
DOI: 10.3390/healthcare9040449
|View full text |Cite
|
Sign up to set email alerts
|

Indices of Cardiovascular Health, Body Composition and Aerobic Endurance in Young Women; Differential Effects of Two Endurance-Based Training Modalities

Abstract: Endurance training (ET) has multiple beneficial effects on cardiovascular health (CVH), but there is an evident lack of knowledge on differential effects of various types of ET on indices of CVH in women. The aim of this study was to analyse the effectiveness of two different types of ET on changes in indicators of CVH in apparently healthy adult women. The sample included 58 women (24 ± 3 years; height: 165 ± 6 cm, mass: 66.7 ± 7.2 kg, BMI: 24.3 ± 2.5 kg/m2, at baseline) divided into one control non-exercisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Physical fitness and body composition are important health indicators for individuals ( Chiriboga & Ockene, 2016 ; Myers et al, 2015 ; Ortega et al, 2018 ), and is shown to improve through physical activities, such as running ( Chalfoun et al, 2016 ; Idrizovic et al, 2021 ). Indeed, running is also associated with improved cardiorespiratory fitness ( Willoughby et al, 2016 ), muscular endurance ( Menz et al, 2019 ), cardiovascular health ( Chalfoun et al, 2016 ; Idrizovic et al, 2021 ), and mental well-being ( Bowler et al, 2010 ; Thompson Coon et al, 2011 ). Furthermore, running also improves mood and helps in exercise adherence ( Oswald et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Physical fitness and body composition are important health indicators for individuals ( Chiriboga & Ockene, 2016 ; Myers et al, 2015 ; Ortega et al, 2018 ), and is shown to improve through physical activities, such as running ( Chalfoun et al, 2016 ; Idrizovic et al, 2021 ). Indeed, running is also associated with improved cardiorespiratory fitness ( Willoughby et al, 2016 ), muscular endurance ( Menz et al, 2019 ), cardiovascular health ( Chalfoun et al, 2016 ; Idrizovic et al, 2021 ), and mental well-being ( Bowler et al, 2010 ; Thompson Coon et al, 2011 ). Furthermore, running also improves mood and helps in exercise adherence ( Oswald et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The lipid profile is one of the most important determinants of CVHS [ 23 , 24 ]. In most common words, lipid profile describes levels of lipids in the blood and most commonly consists of high-density lipoprotein (HDL) cholesterol, low-density lipoprotein (LDL) cholesterol, and triglycerides [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…of women have different family fitness demands [ 16 , 17 , 18 , 19 , 20 ]. For example, women aged 26–35 participate in sports for leisure and in order to accompany their family [ 21 , 22 , 23 , 24 , 25 ]. The top three reasons why women aged 36–45 participate in sports are to strengthen their health [ 26 , 27 ], relieve stress, and accompany their families [ 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%